2016
DOI: 10.2460/ajvr.77.11.1200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of denervation of the hip joint on results of clinical observations and instrumented gait analysis in dogs with sodium urate crystal–induced synovitis

Abstract: OBJECTIVE To evaluate the effects of selective hip joint denervation on gait abnormalities and signs of hip joint pain in dogs. ANIMALS 6 healthy adult hound-type dogs. PROCEDURES Minimally invasive denervation was performed on the right hip joint of each dog. Two weeks later, sodium urate was injected into the right hip joint to induce synovitis. Dogs were evaluated clinically and by use of instrumented gait analysis before and 2 weeks after minimally invasive denervation and 4, 8, and 24 hours after inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
2
1
2
Order By: Relevance
“…Studies using ground reaction force technique showed improvement in smaller percentages of patients [ 22 – 24 ]. One report showed the total ineffectiveness of minimally invasive denervation of the hip joint of in dogs [ 25 ] but unlike previous reports on hip dysplasia in this study pain and lameness were evoked by diffuse synovitis induced with injection of sodium urate into the right hip joint. Unfortunately, these collective studies were performed on small groups of animals (up to 10) making it difficult to draw final conclusions on significant effects.…”
Section: Introductioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Studies using ground reaction force technique showed improvement in smaller percentages of patients [ 22 – 24 ]. One report showed the total ineffectiveness of minimally invasive denervation of the hip joint of in dogs [ 25 ] but unlike previous reports on hip dysplasia in this study pain and lameness were evoked by diffuse synovitis induced with injection of sodium urate into the right hip joint. Unfortunately, these collective studies were performed on small groups of animals (up to 10) making it difficult to draw final conclusions on significant effects.…”
Section: Introductioncontrasting
confidence: 81%
“…Although the efficacy of the medial treatment is quite high a percentage of animals undergoing such denervation of the HJC fail to restore proper function of the joint. This has been suggested to result from insufficient abolition of pain sensation, or diverse hip joint pain cause (e.g., pain originating from the induced diffuse synovitis evoked by use of sodium urate crystal that influence on the efficacy of the denervation procedures [ 25 ]). The severity of degenerative joint diseases can also affect the efficacy of therapy [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As diferenças nas intensidades de redução da dor destes dois testes, comparando MPE e MPD, não foram relevantes (Figura 2). Hassan et al (2016) sugerem que há possibilidade das alterações artríticas mais severas em cães mais velhos venham a progredir para a cápsula articular ventral não desnervada. No entanto, aqui foi observado que a desnervação ventral, mesmo nos 10 animais adultos apresentando DAD, não promoveu melhora adicional quando associada desnervação crânio lateral e ventral, confirmando a teoria que a região crânio lateral é a mais importante como origem de dor, por ser a região mais inervada e receber maior carga de distensão devido à instabilidade (Kinzel et al, 1998).…”
Section: Gruposunclassified
“…2011) realizaram a técnica de desnervação ventral associada a miectomia do músculo pectíneo. Estes autores tiveram bons resultados no alívio da dor, no entanto, os resultados do presente estudo, somados aos estudos anatômicos já realizados, mostrando que a região ventral da cápsula é minimamente inervada e recebe pouca distensão perante a instabilidade (Kinzel et al, 1998;Kinzel et al, 2002;Hassan et al, 2016), leva a crer que a desnervação ventral realizada pelos autores citados teve participação insignificante no alívio da dor e o alívio desta ocorreu apenas nos músculos adutores, que é consequência da dor capsular crânio lateral, não tendo influência de variações nas ramificações nervosas.…”
Section: Gruposunclassified